Non-alcoholic Fatty Liver Disease Induced by Perinatal Exposure to Bisphenol a Is Associated With Activated mTOR and TLR4/NF-κB Signaling Pathways in Offspring Rats - Lin, Ren; Wu, Dan; Wu, Feng-Juan; Meng, Yuan; Zhang, Jin-Heng; Wang, Xiao-Gang; Jia, Li-Hong (Frontiers in Endocrinology, 2019)
Accumulating evidence suggests a role of bisphenol A (BPA) in non-alcoholic fatty liver disease (NAFLD), and its mechanism may be related to the up-regulation of lipogenic genes, but the mechanism of BPA induced lipogenic gene expression remains unknown. The aim of this study was to investigate the effects of perinatal exposure to BPA on NAFLD and its mechanisms. Pregnant Sprague-Dawley rats had access to drinking water containing 1 μg/ml BPA or 10 μg/ml BPA from gestational day 6 to postnatal day 21. For 5 weeks after weaning, offspring drank normal water without BPA. Body weight, lipid profile and the expression of genes or proteins involved in mTOR mediated lipid metabolism and autophagy, as well as inflammatory response were investigated in the 8-wk-old offspring of different genders. The results showed that body weight was increased only in females, however, males and females from dams treated with BPA had significantly excess visceral adipose tissue, which was consistent with adipocyte hypertrophy. Elevated TG levels and up-regulation of lipogenic genes or proteins in liver, such as sterol regulatory element binding protein 1 (SREBP1), acetyl-CoA carboxylase 1 (ACC1), and fatty acid synthase (FAS) were consistent with increased liver lipid droplets in offspring exposed to BPA. Compared with controls, the protein levels of InsR, p-IRS-1, IRS-1, TSC1, and TSC2 were decreased, p-PI3K, p-Akt (S473), p-Akt (T308), p-mTOR and mTOR were increased, and the impaired autophagic degradation was evidenced by increased protein levels of p62, although the levels of p-ULK1, Beclin1 and LC3B proteins were increased in liver of BPA-exposed offspring. The levels of TLR4 and NF-κB proteins were also significantly increased, and ERα protein was significantly decreased in BPA-exposed offspring. Our findings indicate that perinatal exposure to BPA causes the development of NAFLD in both female and male offspring, which is associated with up-regulation of lipogenic genes, dysregulated autophagy and activated inflammatory response involving the PI3K/Akt/mTOR and TLR4/NF-κB pathways.